Kierunki reformy arbitrażu inwestycyjnego w ramach prac Grupy Roboczej III UNCITRAL - Zrałek, Jacek (Problemy Prawa Prywatnego Międzynarodowego, 2020)
The goal of the study is to briefly present the work on the reform of investment arbitration under the auspices of the United Nations Commission on International Trade Law (UNCITRAL) and to indicate the directions in which further discussion on this reform could potentially go. The Commission entrusted to Working Group III to work on the reform of international investment dispute resolution mechanisms. The ongoing debate in this area has met with very little interest in Polish literature. It is surprising since its outcome may have an impact on future investment policy also in Poland. The work is divided into five parts. The first part presents the scope of the work and the research methodology. The second one presents a very concise historical background for the establishment of investment arbitration, taking into account the key features underlying current crisis of this institution. The third part briefly outlines the course of work of UNCITRAL Working Group III. This section provides a background to show how negotiations are progressing, what major obstacles negotiators are facing and what the future direction of the Working Group’s work might be. These issues are discussed in the fourth part of the study. Author’s opinion on anticipated development of further discussion is presented in the closing remarks.